Lack of Cytosolic Glutamine Synthetase1;2 Activity Reduces Nitrogen-Dependent Biosynthesis of Cytokinin Required for Axillary Bud Outgrowth in Rice Seedlings. (10th February 2017) - Ohashi, Miwa; Ishiyama, Keiki; Kojima, Soichi; Kojima, Mikiko; Sakakibara, Hitoshi; Yamaya, Tomoyuki; Hayakawa, Toshihiko
Abstract : A mutation abolishing cytosolic glutamine synthetase1;2 (GS1;2) activity impairs assimilation of ammonium into glutamine in both roots and basal portions of shoots, and severely decreases axillary bud outgrowth (tillering) in mutant rice seedlings. Although the gs1;2 mutant phenotype is independent of strigolactone, which inhibits tillering, it also demonstrates glutamine- or related metabolite-responsive biosynthesis of cytokinin (CK), which promotes tillering. Here, we examined the connection between GS1;2 and CK biosynthesis during tillering, focusing on basal portions of the shoots as well as apical and axillary bud meristems in the gs1;2 mutant. Despite a sufficient ammonium supply, decreases in precursor CK contents and a decrease in ammonium assimilation into glutamine were observed in basal portions of mutant shoots. Reintroducing expression of OsGS1;2 cDNA driven by its own promoter restored precursor CK contents and ammonium assimilation to wild-type levels. In basal portions of the shoots, glutamine-responsive adenosine phosphate-isopentenyltransferase4 ( OsIPT4 ), which is also predominant in rice roots, was the predominant isogene for IPT, which synthesizes CK. Cell-specific expression of OsIPT4 in phloem companion cells in nodal vascular anastomoses connected to the axillary bud vasculature also decreased in the gs1;2 mutant. Expression of CK-responsive type-A response regulator genes as local indicators of active CKs was also abolished in the axillary bud meristem of the mutant. These results suggest that the lack of GS1;2 activity decreased levels of glutamine or a related metabolite required for CK biosynthesis, causing a deficiency in active CK in the axillary bud meristem necessary for tillering.